2014
DOI: 10.1007/s00221-014-4106-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidental self-processing modulates the interaction of emotional valence and arousal

Abstract: The middle insula has been associated with incidental self-processing of negative information elicited by individual's handwriting. However, emotional valence and arousal have been proved to work in an interactive way and located in middle insula. The present functional magnetic resonance imaging study used participant's handwritings as material to explore how incidental self-processing affected the interaction of valence and arousal and its neural basis. Each participant was asked to read silently emotional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Additionally, we found that the insula was positively related to the level of endorsing positive events as self‐relevant, and the dlPFC was negatively related to the level of endorsing positive events as self‐relevant. The insula has been proposed to be involved in self‐related emotion processing (Deen et al., 2011) and the interaction between emotional arousal and valence (Citron et al., 2014; Wang, Zheng, Li, et al, 2015). This suggests that self‐related positive events, which are in line with people's expectations, are likely to attract the attention of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the insula was positively related to the level of endorsing positive events as self‐relevant, and the dlPFC was negatively related to the level of endorsing positive events as self‐relevant. The insula has been proposed to be involved in self‐related emotion processing (Deen et al., 2011) and the interaction between emotional arousal and valence (Citron et al., 2014; Wang, Zheng, Li, et al, 2015). This suggests that self‐related positive events, which are in line with people's expectations, are likely to attract the attention of individuals.…”
Section: Discussionmentioning
confidence: 99%